Discussion of 'Estimating time-varying causal excursion effects in mobile health with binary outcomes'. (12th August 2021) - Kim, S; Cho, H; Bang, D; De Marchi, D; El-Zaatari, H; Shah, K S; Valancius, M; Zikry, T M; Kosorok, M R
Summary: In this discussion, we examine the contributions of Qian et al. (2021) and potential applications of the newly developed estimator for the causal excursion effect in binary outcome data. Specifically, we consider extension of their method to count outcomes and observational data, propose an alternative use of their method for analysing excursion effect trajectories and discuss ways of improving estimator efficiency.